English get-passives: reassessing the frequencies across genres - Supakorn Phoocharoensil (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study investigates the get-passive in American English, with emphasis on its distribution in different text types and its semantic features characterized by co-occurring verbs. The data was drawn from the Corpus of Contemporary American English (COCA), i.e. the latest version with eight different genres. The findings indicate that the get-passive is a linguistic feature of informal English due to its highest frequency in spoken genres, e.g. TV and movie subtitles, and blogs. Furthermore, common verbs constituting the get-passive were explored and their meanings in context were analyzed. In agreement with previous studies, the semantic analysis of get-passives revealed a higher proportion of verbs expressing adversity, followed by those with positive and neutral meanings, respectively. The existence of non-adversative get-passive predicts a decline in the adversative type.